Development of an e-Module Based on a Discovery Learning Model on Form and Function of Body Parts in Plants at Grade IV Elementary School Level - Fitri Khoiroh Sayidah Harahap; Humairoh Sakinah Zainuri; Novia Rahmadani; Siti Fadilla; Windi Melisa; Riska Fadhilah Hutasuhut (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2023)
This research aims to determine the effectiveness of e-module development in the science learning process at the fourth grade elementary school level, especially in the material "Form and Function of Body Parts in Plants". This type of research uses a qualitative method with a descriptive approach which describes the research results into several stages, namely the analysis, design and development stages. From the results of the research that has been carried out, it can be concluded that the use of E-modules in the learning process is very helpful in increasing the effectiveness of learning in order to achieve learning goals. Apart from that, the use of e-module media can also increase students' enthusiasm and interest in understanding learning.